Application for formal testing of PLC program - Sýkora, Ondřej; Arm, Jakub (Vysoké učení technické v Brně, Fakulta elektrotechniky a komunikačních technologií, 2022)
The paper deals with developing application for testing of selected errors contained in Siemens TIA Portal V16 PLC Project. The application is being developed for the company ICE Industrial Services. The application should find bugs that programmers or PLC code generators make, but TIA Portal cannot detect them defaultly. In this moment, application is able to open or find opened TIA Portal project and load its important parts to my structure – ProjectBlocks structure. Application can also find some errors described in Chapter 2.
Keywords: C#, TIA Portal, TIA Portal Openness, Windows form application